Mobi parking navigator system (sensor monitoring) - Sharos Azuanuddin, Mat Sidek (2013)
The vehicles in UMP Gambang Campus keep increasing; problem to get parking spaces is very difficult especially during peak hours. That is also a general problem that occurs in the parking spaces in front of FSKKP building; staff and guest have to circling around the parking spaces a few times to find parking. Mobi Parking Navigator System (Sensor Monitoring Module) is proposed and will be implementing at FSKKP office parking spaces. This system consists of three different modules which are Sensors module (Infrared sensor), Electronic module (Raspberry pi) and System module (Web based system). All the modules will be combining together and build this system full functioning. A system that using an infrared sensor been developed, this system will detect the free parking spaces with infrared sensor and save it to database. Users that have Mobi Parking Navigator System Apps can get information about the parking from this smartphone application. With this system trouble in finding parking spaces will become easier, less cost and less frustration to the driver.